Peran Organisasi BKRM dalam Penguatan Pendidikan Ibadah Generasi Muda di Tanjung Morawa - Fitri, Rizka Aida; Azhar, Ihsan Satrya (Jayapangus Press, 2025)
This study aims to examine the role of the Mosque Youth Coordination Board (BKRM) in strengthening worship education among youth in Tanjung Morawa. BKRM is an active organization that fosters young generations in understanding and practicing Islamic teachings in daily life through various religious and social activities. This research employs a qualitative method with a phenomenological approach. Data were collected through direct observation of religious activities, in-depth interviews with BKRM leaders, members, and mosque youth groups (KRM), and document analysis of program archives. The data were analyzed through data reduction, data display, and conclusion drawing, and were validated using triangulation techniques to ensure data accuracy. The findings indicate that BKRM plays a strategic role in enhancing worship education through programs such as ta’lim, Turba (community outreach), Hijram (Hijratul Muharram), daurah marhala ula, and solidarity actions for Palestine. These programs not only promote conceptual religious understanding but also instill worship values within a social context. BKRM’s success is supported by a spirit of togetherness, a religious social environment, and active guidance from mentors. However, several obstacles were identified, including personal busyness of the youth, lack of individual motivation, distant activity locations, and limited communication. This study concludes that religious organizations such as BKRM make a tangible contribution to strengthening both the understanding and practice of worship among youth. The findings provide practical insights for similar organizations to adopt or adapt BKRM’s youth development model in a more contextual and effective manner.